'And Rome is Rome': Ronald Knox's Virgilian Catholic conversion narrative. (2nd January 2019) - Hartwig, Heidi
ABSTRACT: In 1918, Monsignor Ronald Knox (1888–1957) – English priest, author, theologian and translator – published a spiritual autobiography entitled A Spiritual Aeneid . The immediate fruit of his conversion to Roman Catholicism, it owes its ostensible structure quite untypically, as its title suggests, to Virgil's pre-Christian Aeneid . It is also shaped (negatively) by the Protestant-inflected conversion narrative tradition and by Cardinal John Henry Newman's Catholic conversion narrative Apologia Pro Vita Sua . In tracing these thematic, formal and intertextual influences in Knox's A Spiritual Aeneid, this essay illustrates that Knox represents Catholic conversion as an intersubjective, protracted and rational process – in fact, an essentially Catholic process of intellectual suasion and wilful action – in order to differentiate it from the Protestant conversion narrative tradition. Far from being merely defensive, however, Knox's differentiation from his own former Anglican self and community is subtly eirenic. In A Spiritual Aeneid, Knox successfully reconciles the predominantly English Protestant form and the Roman Catholic variant of Newman's Apologia Pro Vita Sua, mainly by using the extrinsic Latin of Virgil in multiple ways – allegorically, stylistically and, finally, sacramentally.